2018
DOI: 10.15252/emmm.201708772
|View full text |Cite
|
Sign up to set email alerts
|

Selective depletion of metastatic stem cells as therapy for human colorectal cancer

Abstract: Selective elimination of metastatic stem cells (MetSCs) promises to block metastatic dissemination. Colorectal cancer (CRC) cells overexpressing CXCR4 display trafficking functions and metastasis‐initiating capacity. We assessed the antimetastatic activity of a nanoconjugate (T22‐GFP‐H6‐FdU) that selectively delivers Floxuridine to CXCR4+ cells. In contrast to free oligo‐FdU, intravenous T22‐GFP‐H6‐FdU selectively accumulates and internalizes in CXCR4+ cancer cells, triggering DNA damage and apoptosis, which l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 70 publications
(103 citation statements)
references
References 51 publications
1
88
0
Order By: Relevance
“…To this end, we have selected the functionalization of T22‐GFP‐H6 protein with oligonucleotides carrying several units of FdU using the method based on the thiol‐maleimide reaction. We have demonstrated that this conjugate showed antitumor but specifically antimetastatic activity in a CXCR4+ metastatic colorectal cancer model …”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…To this end, we have selected the functionalization of T22‐GFP‐H6 protein with oligonucleotides carrying several units of FdU using the method based on the thiol‐maleimide reaction. We have demonstrated that this conjugate showed antitumor but specifically antimetastatic activity in a CXCR4+ metastatic colorectal cancer model …”
Section: Methodsmentioning
confidence: 98%
“…It is worth to mention that in the case of BSA in spite of being a bigger protein than T22‐GFP‐H6 the DLS data indicate a smaller size (7.4 nm) compared with T22‐GFP‐H6. This is because T22‐GFP‐H6 self‐assemble to produce a larger protein nanoparticle ,…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we specifically tested if a novel T22-GFP-H6-Auristatin nanoconjugate (NC) selectively eliminates CXCR4+ AML cells, and therefore LSCs, in an AML disseminated model, to improve chemotherapy performance, which reduces the differentiated tumor bulk but does not eliminate LSCs [20]. The NC incorporates a protein nanoparticle to selectively internalize in CXCR4+ AML cells by exploiting high CXCR4 overexpression in LSCs as compared to HSCs [6,20], similarly to a previous approach in colorectal cancer (CRC) [21,22]. The NC is loaded with Auristatin E, a microtubuledestabilizing toxin, introduced in clinical oncohematology [23,24].…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
“…In this context, and to explore in detail the potential systemic use of IBs as a novel drug‐releasing material, we administered T22‐PE24‐H6 IBs to metastatic mouse models derived from human colorectal and based on CXCR4 + SW1417‐luciferase expressing cells . Note that as previous reference, we had determined the biodistribution of a fluorescent protein material released from IBs formed by T22‐empowered GFP, which followed the expected biodistribution and tumor accumulation .…”
Section: Reduction Of Metastatic Foci Induced By Pe24 Ibs Treatmentmentioning
confidence: 99%